Ethical Traceability and Communicating Food
XXVI, 318 p.
Keywords: Traceability – the ability to track a product from farm to plate – is now widely used in the food sector for a range of purposes: it allows companies to improve efficiency, facilitates product recall, and helps producers flag the specific characteristics of their goods. But traceability systems are mainly designed and used by the people directly involved in the food chain. The people at the end of the food chain – food consumers – have little say in which attributes are traced, and can rarely access the information stored in traceability systems. This book draws on philosophical discourses (like ethics, political philosophy and philosophy of law) around food ethics and empirical research in three important food chains (UK bread, Danish bacon and Greek olive oil) to argue that ethical traceability systems could be used to communicate food information to consumers, allowing them not only to make food choices consistent with their own values, but also to play a more informed role in the way food is produced and distributed. It will appeal to academics, students and policy makers with an interest in traceability, food ethics and food policy.